2018
DOI: 10.1016/j.diabres.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of glycated albumin as a biomarker for glucose control and prognostic factor in chronic kidney disease patients on dialysis (CKD-G5D)

Abstract: In chronic kidney disease patients on dialysis (CKD-G5D) accurate assessment of glycemic control is vital to improve their outcome and survival. The best glycemic marker for glucose control in these patients is still debated because several clinical and pharmacological factors may affect the ability of the available biomarkers to reflect the patient's glycemic status properly. This review discusses the role of glycated albumin (GA) both as a biomarker for glucose control and as a prognostic factor in CKD-G5D; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
0
9
2
Order By: Relevance
“…Considering that GA is a product of glycation that reflects early changes in glycemic control [33], the increased levels observed in DM should be considered a direct consequence of a worsened glycemic control and oxidative stress. Furthermore, GA seems a more reliable marker for glycemic control in CKD patients in which HbA1c suffers some limits, because it can both under-and over-estimate a patient's glycaemia, depending on the disease state and drug therapy [22]. Differently from previous studies in dialysis patients [22], we found no evidence of association of GA with all-cause mortality, although not so far from statistical significance.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Considering that GA is a product of glycation that reflects early changes in glycemic control [33], the increased levels observed in DM should be considered a direct consequence of a worsened glycemic control and oxidative stress. Furthermore, GA seems a more reliable marker for glycemic control in CKD patients in which HbA1c suffers some limits, because it can both under-and over-estimate a patient's glycaemia, depending on the disease state and drug therapy [22]. Differently from previous studies in dialysis patients [22], we found no evidence of association of GA with all-cause mortality, although not so far from statistical significance.…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, GA seems a more reliable marker for glycemic control in CKD patients in which HbA1c suffers some limits, because it can both under-and over-estimate a patient's glycaemia, depending on the disease state and drug therapy [22]. Differently from previous studies in dialysis patients [22], we found no evidence of association of GA with all-cause mortality, although not so far from statistical significance. Therefore, our data cannot definitively exclude that GA may have a prognostic role on mortality in CKD patients not yet on dialysis.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…As GA is not affected by the same limitations as hemoglobin, it may be an acceptable alternative biomarker of glycemic control when HbA1c is unreliable as in CKD, particularly during hemodialysis [302]. It also seems to be a better predictor of cardiovascular complications and risk of hospitalization or death in these patients when HbA1c is especially unreliable in the presence of anemia or erythropoietin administration [303,304].…”
Section: Glycated Albuminmentioning
confidence: 99%
“…Both fructosamine and GA are the markers of choice when glycemic control needs to be assessed in patients with severe chronic kidney disease (CKD) (stages 4 and 5)[80]. Additionally, in stage 5 CKD patients on hemodialysis, GA can be used as a predictor of overall survival and cardiovascular mortality[81]. Due to the reduced production and lifespan of red blood cells and to erythropoietin treatment in CKD patients, HbA1c cannot be used as reliable marker, as it can significantly underestimate the true glycemic status in these patients[82].…”
Section: Glycated Proteinsmentioning
confidence: 99%